2020
DOI: 10.1002/bse.2607
|View full text |Cite
|
Sign up to set email alerts
|

The management of sustainable development: A longitudinal analysis of the effects of environmental performance on economic performance

Abstract: The literature on sustainable development has largely focused on investigating the relationship between companies' environmental and economic performance. However, many aspects remain unexplored, and empirical studies are far from reaching a consensus due to the heterogeneity of the environmental and economic measures and methodologies used. This study contributes to the literature on sustainable development by considering a panel of 998 US companies observed over the period 2003–2017 using both traditional pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 80 publications
(88 reference statements)
3
38
0
Order By: Relevance
“…The literature on evaluation of sustainability has largely focused on investigating environmental and economic potential. In this regard, Bassetti, Blasi and Sedita [4] researched interconnection among environmental conditions and economic performance. The empirical evidence confirmed that well-advised environmental orientation positively affects economic situation of nations and contribute to future well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on evaluation of sustainability has largely focused on investigating environmental and economic potential. In this regard, Bassetti, Blasi and Sedita [4] researched interconnection among environmental conditions and economic performance. The empirical evidence confirmed that well-advised environmental orientation positively affects economic situation of nations and contribute to future well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of Bassetti et al (2020) convey how environmental performance, measured in terms of environmental orientation and environmental innovation, positively impacts returns on assets and net equity. Furthermore, these returns depend on the capacity of green firms to generate the same revenue flows as their non‐green counterparts but through less capital.…”
Section: Resultsmentioning
confidence: 99%
“…This study contributes to both the academic literature and corporate governance for banks in several respects. First, most of the previous scientific research that has focused on climate‐related action and governance has mainly referred to nonfinancial institutions (Albertini, 2013; Bassetti et al, 2020; Naciti, 2019), whereas this paper takes the banking sector into account. Second, to the best of our knowledge, most of the existing evidence on the banking sector refers to the link between governance variables and FP or CSR (Coulson, 2009; Khatib et al, 2020; Orazalin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, plenty of empirical studies have been conducted on the relationship between social and EP against FP (Bassetti et al, 2020;Duque-Grisales & Aguilera-Caracuel, 2019;Duque-Grisales et al, 2020;Garcia & Orsato, 2020;Minutolo et al, 2019;Qureshi et al, 2020;Xie et al, 2019). Several studies have proved the existence of a positive relationship between corporate environmental performance (CEP) and corporate financial performance (CFP) (Albertini, 2013;Dixon-Fowler et al, 2013 Orlitzky et al, 2003;Raut et al, 2017).…”
Section: Financial Institutions and Climate Changementioning
confidence: 99%